2021
DOI: 10.3389/fmicb.2021.547020
|View full text |Cite
|
Sign up to set email alerts
|

Plasmid Mediated mcr-1.1 Colistin-Resistance in Clinical Extraintestinal Escherichia coli Strains Isolated in Poland

Abstract: Objectives: The growing incidence of multidrug-resistant (MDR) bacteria is an inexorable and fatal challenge in modern medicine. Colistin is a cationic polypeptide considered a “last-resort” antimicrobial for treating infections caused by MDR Gram-negative bacterial pathogens. Plasmid-borne mcr colistin resistance emerged recently, and could potentially lead to essentially untreatable infections, particularly in hospital and veterinary (livestock farming) settings. In this study, we sought to establish the mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 104 publications
1
6
0
Order By: Relevance
“…The distribution and genetic identification of resistance genes among individual plasmid types across different bacterial strains have been documented ( Venturini et al, 2013 ; Carattoli et al, 2015 ; Reid et al, 2015 ; Seiffert et al, 2017 ; Moran and Hall, 2019 ; Chang et al, 2020 ; Majewski et al, 2021 ). In the current study, we applied several bioinformatic tools including BLAST, AMRFinderPlus, and ISFinder for detecting genes in assembled plasmid sequence data and assessed the combination of resistance genes and MGEs, and individual plasmid types from enteric bacterial species to better elucidate AMR epidemiology as an effort to respond to this important public health threat.…”
Section: Introductionmentioning
confidence: 99%
“…The distribution and genetic identification of resistance genes among individual plasmid types across different bacterial strains have been documented ( Venturini et al, 2013 ; Carattoli et al, 2015 ; Reid et al, 2015 ; Seiffert et al, 2017 ; Moran and Hall, 2019 ; Chang et al, 2020 ; Majewski et al, 2021 ). In the current study, we applied several bioinformatic tools including BLAST, AMRFinderPlus, and ISFinder for detecting genes in assembled plasmid sequence data and assessed the combination of resistance genes and MGEs, and individual plasmid types from enteric bacterial species to better elucidate AMR epidemiology as an effort to respond to this important public health threat.…”
Section: Introductionmentioning
confidence: 99%
“…The co-resistance of mcr-1 colistin-resistance E. coli to β-lactams, fluoroquinolone, aminoglycoside, folate pathway antagonist was also reported in clinical E. coli strains in Poland (Majewski et al, 2021), and…”
Section: Discussionmentioning
confidence: 88%
“…Subsequently, we tested whether this newly observed bimodal distribution of tachyplesin-NBD accumulation was unique to the E. coli BW25113 strain. We found that the bimodal distribution in single-cell fluorescence was also present in nine E. coli clinical isolates (treated with tachyplesin-NBD at 46 μg mL -1 for 60 min) characterised by a diverse genetic background and various antimicrobial resistance genes, such as the polymyxin-E resistance gene mcr1 38 (Figure 1B, 1C and Data Set S1). The low accumulator median in strains JD1147 and MC04960 were shifted to the left and to the right, respectively, compared to BW25113, whereas the high accumulator median in the distribution for strain JS1060 was shifted to the left compared to BW25113.…”
Section: Tachyplesin Accumulates Heterogeneously Within Clonal E Coli...mentioning
confidence: 83%